The Effect of Sacrificial Agents in the Photodegradation of Methylene Blue Using Ag-Fe3O4 Nanoparticles - Frisellya Dirgantari; Nasikhudin; Herlin Pujiarti; Markus Diantoro (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2026)
Organic dyes in water are hazardous pollutants due to their toxic properties. One method capable of decomposing these pollutants is photocatalysis. Magnetite (Fe₃O₄) is an iron oxide that can be used as a photocatalyst material and synthesized using the coprecipitation method. These properties facilitate the separation of impurities from the medium. However, Fe₃O₄ has limited photocatalytic activity, so it needs to be composited with silver (Ag) to increase light absorption. Ag material can be produced using AgNO₃ as a source of silver ions. The resulting catalyst, with the addition of Sacrificial Agent solutions, was tested for photocatalytic Methylene Blue solution. The XRD, EDX, SEM, and Photocatalytic characterization results showed a crystalline Fe₃O₄ structure and appropriate material composition. This study demonstrates that adding Ag can enhance the photocatalytic activity of Fe₃O₄, while adding SA can minimize electron-hole recombination and increase the MB degradation efficiency.